Just for future reference always put ^ for exponents. The answer is y-6 though.
(y-4)(y-6) create that trinomial. You can prove that by using the FOIL algorithm
Answer:the answer is B
Step-by-step explanation:Bisect each of the angles with vertices at their houses
Answer:
- 1
Step-by-step explanation:
8m + 5n
8(3) + 5(- 5)
24 + (- 25)
24 - 25
- 1
Answer:
y = 1/2 (2)x
Step-by-step explanation:
Using the equation y = abx , substitute both of your given points into that equation.
2 = ab2 and 4 = ab3 Solve each equation for a.
2⁄b2 and 4⁄b3 = a Therefore, 2⁄b2 = 4⁄b3
Cross multiply: 2b3 = 4b2 Divide both sides by b2
2b = 4 a = 2/4 = 1/2
b = 2